Dangerised youth: the politics of security and development in Timor-Leste. Issue 4 (3rd April 2019) - Distler, Werner
Abstract: International organisations, the national government and civil society alike have identified youth as a potential threat to the stability of the young state of Timor-Leste over the last decade. In this article, I ask how these actors define the danger of youth and what reasons they identify for the potential threat of young citizens for the society and state. Guided by a theoretical framework of Critical Security and Development Studies, I argue that while political manipulation as reason for youth violence was a prominent part of the security discourse in the years after the crisis in 2006, the discourse on the danger of youth in very recent international and national documents has been depoliticised. Despite decreasing numbers of youth-related violence, the threat construction has not vanished; rather, the language on youth has been adapted to the existing international discourse on violent youth as a threat to successful development. In this way, international and national actors have sustained the image of a society in need of management.